2011
DOI: 10.1073/pnas.1017275108
|View full text |Cite
|
Sign up to set email alerts
|

Prion-like propagation of mutant superoxide dismutase-1 misfolding in neuronal cells

Abstract: Deposition of proteins of aberrant conformation is the hallmark of many neurodegenerative diseases. Misfolding of the normally globular mutant superoxide dismutase-1 (SOD1) is a central, early, but poorly understood event in the pathogenic cascade leading to familial forms of ALS. Here we report that aggregates composed of an ALS-causing SOD1 mutant penetrate inside cells by macropinocytosis and rapidly exit the macropinocytic compartment to nucleate aggregation of the cytosolic, otherwise soluble, mutant SOD1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
431
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 429 publications
(450 citation statements)
references
References 38 publications
16
431
2
1
Order By: Relevance
“…In people with SOD1-mediated familial ALS, mutant SOD1 protein may be a diagnostic or prognostic biomarker [48,49]. Misfolded SOD1 could potentially also be a target in sporadic ALS.…”
Section: Toward Novel Outcome Measures and Biomarkers In Als Trialsmentioning
confidence: 99%
“…In people with SOD1-mediated familial ALS, mutant SOD1 protein may be a diagnostic or prognostic biomarker [48,49]. Misfolded SOD1 could potentially also be a target in sporadic ALS.…”
Section: Toward Novel Outcome Measures and Biomarkers In Als Trialsmentioning
confidence: 99%
“…the intercellular transfer of misfolded proteins has recently been demonstrated in several neurodegenerative diseases, including aLS [1][2][3], and it has been suggested that this mechanism is responsible for the progressive spread of pathology. Mutations in SOD1 (Cu/Zn-superoxide dismutase) cause 20 % of familial aLS, and these cases display similar clinical features and pathogenesis to sporadic aLS, which accounts for 90 % of all aLS cases.…”
Section: Introductionmentioning
confidence: 99%
“…SOD1 is secreted by neuronal cells [12,13] and is present in the cerebrospinal fluid (CSF) of aLS patients [14,15]. aggregated mutant SOD1 can be taken up by cells via macropinocytosis which triggers subsequent aggregation of natively folded SOD1 [1]. Similarly, extracellular misfolded SOD1 Wt induces cell death [16] and overexpression of SOD1 Wt induces misfolding of natively folded SOD1 in human but not mouse neuronal cell lines, demonstrating species specificity in the transfer of misfolding [17].…”
Section: Introductionmentioning
confidence: 99%
“…In neural cells, SOD1 localized to endosomes after internalization, but could escape to induce native cytosolic SOD1 to aggregate. This templated misfolding persisted for at least a month, well after the original internalized aggregates were no longer detectable [77]. SOD1 seeds can also be found in the CSF of mice that over-express an aggregate-prone mutant form of the protein, and these seeds can induce new fibril formation of recombinant SOD1 in vitro [78].…”
Section: Spreading Pathology In Alsmentioning
confidence: 99%
“…Furthermore, it was recently observed that SOD1 fibrils can transfer between cells and be taken up via clathrinindependent macropinocytosis [77]. In neural cells, SOD1 localized to endosomes after internalization, but could escape to induce native cytosolic SOD1 to aggregate.…”
Section: Spreading Pathology In Alsmentioning
confidence: 99%